Evaluating agency use of "best available science" under the United States Endangered Species Act. (April 2016) - Lowell, Natalie; Kelly, Ryan P.
Abstract: The United States Congress passed the Endangered Species Act (ESA) in 1973, a law aimed at preventing the extinction of rare species. Since then, the ESA has become increasingly politicized in the U.S., adding to the difficulty of ESA implementation and endangered species management, while species continue to go extinct at alarming rates. The ESA is among the first statues to include a "best available science" mandate, requiring that agencies use the best scientific and commercial data to guide key decisions. Because the way in which agencies use science under the ESA is often the legal basis for litigation, it is timely and pertinent to evaluate the federal agencies' sources of information—and their uses of this information. The "best" available science and its use are each moving targets, difficult to define in the abstract. However, a straightforward way of evaluating these ideas is to compare the use of science by each of the two administrative agencies in charge of implementing the ESA, the Fish and Wildlife Service (FWS) and the National Oceanic and Atmospheric Administration's National Marine Fisheries Service (NOAA). Here, we use bibliographic data, litigation records, authorship affiliation, and related data to ask whether the two agencies' use of scientific information differs systematically. Overall, we find that NOAA draws more deeply from the scientific literature and is somewhat better buffered from changes in political administration than is FWS. These results suggest NOAA's implementation is more closely aligned with commonly held ideas of good scientific practice than that of FWS, although in some cases these differences could also result from the different amounts of available information on the species each agency manages. We then interpret these findings in the context of each agency's budget, structure, and history and highlight specific policy mechanisms that would allow the agencies to improve endangered species management, and reduce their own exposure to litigation, by improving their use of high-quality scientific information.